IMPROVING ELECTRONIC COMMERCE IN THE DIGITAL ECONOMY - Yuldasheva Saodat Arislanovna; Rakhimberdiyev Ismoil Ubadydullayevich (Web of Journals Publishing, 2023)
The article examines the relationship between the use of act technologies in the organization of electronic commerce and the introduction and use of digital technologies using information communication systems. During the research, a system for ensuring information security was developed in the realization of products of industrial enterprises through electronic commerce.
Keywords: Electronic commerce, information system, enterprise management, automation, system efficiency, management decisions, management modules, software tools, integrated information system, information communication technologies.